Enhancing Social Interaction Through Group Guidance Services - Susi Hardianti; Widya Kartika Sari; Nurul Jannah; Winda Ade Ariani (Universitas Muria Kudus, 2024)
Good student social interactions will create harmonious relationships. Form of social interaction that can be seen with cooperation, mutual respect and mutual support. Collaboration is increasingly created when a difficulty is found in the learning process at shool. Students will help each other discuss and help each other. Good social conversation between students can also create muntul support and create comfort related to learning and will encourage students to excel in the school environment. Ideally, students can interact the learning process (both iin the classroom and ounside the classroom) with a sense of joy, and enjoy all academic activities that they live. That way, all the energy they can get involved in the learning process that they follow, so the learning outcomes they get are satisfactory results. This study aims to improve the social abilities of students of SMA N 07 Bengkulu city.